2015
DOI: 10.1590/s0080-623420150000400004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding child neglect in a gender context: a study performed in a Brazilian city

Abstract: Objective:To describe the phenomenon of child neglect and understand it in a gender context. Method: Retrospective, quantitative, and exploratory study that analyzed reports of violence by a child and adolescent protection network in a Brazilian city. The theoretical and methodological basis applied was TIPESC (Theory of Nursing Praxical Intervention in Collective Health), with a gender emphasis. Results: Neglect of children under the age of ten represents more than half the reports received over all the years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
26

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 10 publications
3
21
1
26
Order By: Relevance
“…Thus, professionals are concerned not to invade into the private space of families (17) . We also emphasize the very positive conception of professionals regarding the family and their social role, even though some studies have shown that many situations of violence, abuse and neglect against children and adolescents are experienced in the family environment/household, and parents or people with intimate relationships to the family are the main perpetrators (17)(18) . Often violent or negligent acts go unnoticed by professionals who end up allowing that the violence continues to be perpetrated in the family environment, as shown in a study carried out with American doctors who consider physical punishment acceptable under certain circumstances (11) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, professionals are concerned not to invade into the private space of families (17) . We also emphasize the very positive conception of professionals regarding the family and their social role, even though some studies have shown that many situations of violence, abuse and neglect against children and adolescents are experienced in the family environment/household, and parents or people with intimate relationships to the family are the main perpetrators (17)(18) . Often violent or negligent acts go unnoticed by professionals who end up allowing that the violence continues to be perpetrated in the family environment, as shown in a study carried out with American doctors who consider physical punishment acceptable under certain circumstances (11) .…”
Section: Discussionmentioning
confidence: 93%
“…These results are similar to those obtained in a study conducted in England that found that the expectations regarding the mother figure go beyond caring for children; that is, they also become responsible for managing the father's and other family members' behavior (20) . For some authors, such attitudes may be guided by the social construction of gender, where men are connected to the sphere of economic and political life, while women take responsibility for the private sphere of the home, and so the caring for children shall be entirely their responsibility (18,21) . As a consequence, professional practices facing situations of interfamily violence tend to not include mothers and fathers in the intervention process, thus only being responsible for the immediate care of the victims.…”
Section: Discussionmentioning
confidence: 99%
“…O estudo de Egry et al, (2015) Essa teoria permite compreender como cada sociedade cria determinados padrões de desgastes e fortalecimentos em função dos modos de produção e reprodução social (Fonseca, Egry e Bertolozzi, 2006). Desse modo, a visão de mundo trazida por essa teoria pode ajudar a superar as lacunas, no que tange ao reconhecimento de necessidades dos diferentes grupos sociais e a elucidação dos fenômenos sociais, como a violência.…”
Section: Multicausalidadeunclassified
“…[ (Saunders, Goodall, 1985;Carlos, Ferriani, 2016;Egry et al 2015;Egry, Fonseca, Oliveira, 2013;Barrientos, 1998;Lourenço, 2018;Fornari, 2019).…”
Section: Multicausalidadementioning
confidence: 99%
“…Al no ser una meta explicita a lograr en los objetivos sanitarios, la identificación y notificación se hace más compleja, sucediendo lo mismo que en otros países, como Francia, en donde el maltrato sigue siendo subestimado (96) . Al no haber un proceso de notificación de la violencia, es complejo saber su magnitud, en las distintas etapas del ciclo vital de niños, niñas y adolescentes, perpetuando así su invisibilidad (97,98) , quedando, de este modo, solo los datos estadísticos que corresponden a casos más graves de violencia.…”
Section: Las Potencialidades Y Limitaciones De Las Políticas De Enfreunclassified